2013
DOI: 10.1186/1749-8090-8-159
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Masimo Pronto-7® system in patients with left ventricular assist device

Abstract: BackgroundThe Masimo Pronto-7® calculates hemoglobin (Hb) values using the pulsoximetry technique and a variety of mathematical algorithms analyzing the pulse waveform. Although this system has demonstrated a high level of accuracy in average patients, the performance might be altered in special patient populations. Regarding patients with left ventricular cardiac failure, a rotary blood pump generates a constant, continuous, non-pulsatile flow to improve effective cardiac output. Due to this alteration in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…5A and C). Eleven studies included 13 comparisons between the reference and the Masimo Radical-7 with the reference among children aged 3 years and 12−17 years and adult males and females aged 18 years and older 41,43,107,116,[123][124][125][126][127][128] (Fig. 5A).…”
Section: Figure 4 Differences In Mean Hb Of the Other Invasive Pointmentioning
confidence: 99%
See 1 more Smart Citation
“…5A and C). Eleven studies included 13 comparisons between the reference and the Masimo Radical-7 with the reference among children aged 3 years and 12−17 years and adult males and females aged 18 years and older 41,43,107,116,[123][124][125][126][127][128] (Fig. 5A).…”
Section: Figure 4 Differences In Mean Hb Of the Other Invasive Pointmentioning
confidence: 99%
“…107 Ten studies with 11 comparisons analyzed venous blood with six comparisons finding a lower mean Hb concentration (1.4−10.0 g/L) and five comparisons having a higher mean Hb concentration (1.2−7.0 g/L) by Radical-7 compared with the reference. 43,53,104,123,124,[126][127][128] Von Schweinitz et al also analyzed venous blood by the Masimo Radical-57 compared with the reference finding a higher mean Hb concentration (12.0 g/L) by the Masimo Radical-57 (data not shown). 125 When applying the variation in mean difference threshold of ±7% to the studies comparing the Masimo Radical-7 with the reference, nine studies 41,43,53,104,116,124,125,127,128 were within the allowable range of variation and four studies exceeded the ±7% bias range 43,107,123,126 (Fig.…”
Section: Figure 4 Differences In Mean Hb Of the Other Invasive Pointmentioning
confidence: 99%
“…Bruells et al 15 reported a low bias of .14 g/dL between the invasive reading and noninvasive Hb readings but noted increased inaccuracy in patients with an Hb level less than 7.5 g/dL when evaluating patients with continuous flow left ventricular assist devices. In contrast, Joseph et al compared the Pronto-7 spot-check Hb device to standard laboratory Hb measurements in trauma patients arriving at the emergency department in a level 1 trauma center and found a strong correlation (r 5 .77), and on subanalysis of patients by anemia (Hb %8 g/dL and Hb .8 g/ dL), there was strong correlation between invasive and noninvasive Hb measurement in patients with Hb greater than 8 g/dL (r 5 .79; P 5 .03).…”
Section: Commentmentioning
confidence: 96%
“…Radical-7 and Pronto-7 produced by Masimo Corporation could accomplish non-invasive Hb real-time monitoring. [15][16] Though near infrared non-invasive Hb measurement technology has developed tremendously, and numerous researches and practices have been achieved, the not intensely excellent measurement precision and stability are the important obstacles hindering widespread application of this technology in clinic. 4 Now, weak valid spectra signal and strong background interference have become the primary problems which obstacle the development of near infrared non-invasive detection, leading to a difficulty for precision of near infrared non-invasive Hb measurement to meet the requirements of clinical applications.…”
Section: Introductionmentioning
confidence: 99%